Prevalence of Vitamin B12 Deficiency in Libyan Type 2 Diabetic Patients Treated with Metformin - Gamag, Elmabruk; Alsalmi, Waled (AlQalam Journal of Medical and Applied Sciences, 2024)
Metformin is the most-used drug in type 2 diabetes mellitus management and its long-term use may consequent to vitamin B12 deficiency. The lack of studies from Libya investigating the risk of association between these two presents a gap in our understanding of this issue. Our study aimed to estimate the prevalence of vitamin B12 deficiency in metformin treated diabetic patients and non-metformin treated patients and its correlation with diabetic duration and gender. Specifically, we tested the hypothesis that T2DM patients treated with metformin exhibit a decrease in vitamin B12 levels and are considered at risk for developing B12 deficiency depending on the diabetic duration and metformin use. A total of 81 samples of metformin treated diabetic patients (N=58) and non-metformin diabetic treated patients (N=23) were collected and underwent assessment of F.B.S, HbA1c and B12 level. The total mean age was 46.4± 8.27 (47.25± 9.22 for males and 45.55± 7.32 for males respectively). Total mean and standard deviation of blood glucose level was 173.93± 29.87 mg/dl (158.25± 27.35 and 184.18± 27.06 for males and females, respectively). Total mean and standard deviation HbA1c level was 6.81± 1.98% (5.94± 1.31 and 7.37± 2.14 for males and females, respectively). Total mean and standard deviation of vitamin B12 level was 435.53± 251.31 (575.62± 250.21 and 342.76± 205.91 for males and females, respectively). Our study indicated that the shortage of vitamin B12 was generally found in our population, insufficient vitamin B12 level was frequently reported in metformin administration to patients with T2DM and could progress into deficiency. Further larger studies are required to assess vitamin B12 level in those patients. يعتبرالميتفورمين من أكثرالادوية استخداما في علاج مرض السكري من النوع الثاني لكن استخدامه على المدى الطويل قد يؤدي إلى نقص فيتامين ب 12. إن عدم وجود دراسات من ليبيا تبحث في خطر الارتباط بين هذين الأمرين يمثل فجوة في فهمنا لهذه الموضوع. هدفت دراستنا إلى تقدير مدى انتشار نقص فيتامين ب 12 لدى مرضى السكري المعالجين بالميتفورمين والمرضى غير المعالجين بالميتفورمين وارتباطه بمدة الإصابة بالسكري والجنس. على وجه التحديد، قمنا باختبار الفرضية القائلة بأن مرضى السكري الذين عولجوا بالميتفورمين يظهرون انخفاضًا في مستويات فيتامين ب 12 ويعتبرون معرضين لخطر الإصابة بنقص ب 12 اعتمادًا على مدة الإصابة بالسكري واستخدام الميتفورمين. تم جمع 81 عينة من مرضى السكري منهم 58 يعالجون بالميتفورمين و23 عسنة لايعالجون بالميتفورمين. بلغ متوسط العمر الإجمالي 46.4±8.27 (47.25±9.22 للذكور و45.55±7.32 للاناث على التوالي). كان المتوسط الإجمالي والانحراف المعياري لمستوى الجلوكوز في الدم 173.93 ± 29.87 ملغم / ديسيلتر (158.25 ± 27.35 و 184.18 ± 27.06 للذكور والإناث على التوالي). كما أن المتوسط الاجمالي والانحراف المعياري لمستوى كان HbA1c 6.81 ± 1.98٪ (5.94 ± 1.31 و 7.37 ± 2.14 للذكور والإناث على التوالي. كماأن المتوسط الإجمالي والانحراف المعياري لمستوى فيتامين ب 12 435.53 ± 251.31 (575.62 ± 250.21 و 342.76 ± 205.91 للذكور والإناث على التوالي). أشارت دراستنا إلى أن النقص في فيتامين ب12 موجود بشكل عام في مجتمعنا، وقد تم الإبلاغ عن عدم كفاية مستوى فيتامين ب12 بشكل متكرر عند تناول الميتفورمين للمرضى الذين يعانون من السكري ويمكن أن يتطور إلى نقص حاد